Sensitivitas Pemeriksaan Covid-19: Insulated Isothermal PCR (iiPCR) Dan Reverse Transcription PCR (RT-PCR) - Lisa Yunita; Dian Rachma Wijayanti; Apriani Riyanti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
Covid-19 (Corona Virus disease 2019) is a new type of disease caused by a virus from the Corona Virus group, namely SARS-CoV-2. Covid-19 may cause respiratory system disorders, ranging from mild symptoms such as flu to lung infections, such as pneumonia. Laboratory diagnoses for Covid-19 disease generally include hematological (complete blood examinations), and molecular or a combination of serology and molecular. PCR examination that can be carried out using the Insulated Isothermal PCR and Reverse Transcription PCR methods. This research is descriptive observational research. Data were collected at Grha Kedoya Hospital, West Jakarta, North Kedoya. The result showed a sensitivity of iiPCR score 82,6%, which is relatively lower than gold-standard RT-PCR. Our research suggested that RT-PCR is still an effective and sensitive method for Covid-19 examination.